Clinical effects of midazolam or lidocaine co-induction with a propofol target-controlled infusion (TCI) in dogs. (September 2016) - Minghella, Enzo; Auckburally, Adam; Pawson, Patricia; Scott, Marian E; Flaherty, Derek
Abstract: Objective: To evaluate the propofol requirement, cardiovascular and respiratory variables using midazolam or lidocaine with a propofol target-controlled infusion (PTCI) for induction of anaesthesia in healthy dogs. Study design: Prospective, randomized, controlled blinded clinical trial. Animals: Sixty client-owned dogs [American Society of Anesthesiologists (ASA) I–II] undergoing surgical procedures. Methods: Thirty minutes after premedication with acepromazine (0.03 mg kg −1 ) and morphine (0.2 mg kg −1 ), PTCI was started and maintained at a plasma target concentration of 1 μg mL −1 . Three minutes later, dogs ( n = 20 per group) received either 5 mL 0.9% sodium chloride (SG), 2 mg kg −1 of lidocaine (LG) or 0.2 mg kg −1 of midazolam (MG) intravenously (IV) as a co-induction agent. Two minutes later, suitability for endotracheal intubation was assessed. If intubation was not possible, the propofol target was increased by 0.5 μg mL −1 every 60 seconds until it was successfully achieved. Heart rate (HR), respiratory rate ( f R ), and oscillometric systolic arterial pressure (SAP), mean arterial pressure (MAP) and diastolic arterial pressure (DAP) were recorded immediately prior to commencing PTCI (B0), prior to intubation (BI), immediately after (T0), and at 3 (T3) and 5 (T5) minutes post-intubation. End-tidal partial pressures of carbon dioxide (PE ′ CO2 ) were recorded at T0, T3 and T5. The occurrence of excitement at any time point was noted. Results: The median (range) propofol target concentration for endotracheal intubation was significantly lower in MG, 1.5 (1.0–4.0) μg mL −1 compared with LG, 2.5 (1.5–4.5) μg mL −1 or SG, 3.0 (2.0–5.0) μg mL −1 . Heart rate, MAP, f R and PE ′ CO2 were similar in the three groups at all time points. No excitement was reported in any dog. Conclusions and clinical relevance: Midazolam, but not lidocaine, provided a significant reduction in PTCI requirement for induction of anaesthesia thereby allowing successful intubation. However, cardiovascular and respiratory effects were not different between the groups.